Pengaruh Islamic Corporate Governance, Jumlah Modal Inti, dan Jumlah Kantor Pelayanan Terhadap Market Share Bank Umum Syariah Tahun 2016-2020 - Yolandha Dewi Rosestino; Rohmawati Kusumaningtias (UNIVERSITAS NUSANTARA PGRI KEDIRI, 2022)
This research aims to verify the influence of Islamic Corporate Governance (ICG), the amount of core capital, and the number of service offices on the market share of Islamic Commercial Banks (BUS) in Indonesia as measured by the total assets of Islamic Commercial Banks to the total assets of the national banking system. The population in this research is Islamic Commercial Banks registered at OJK in the 2016-2020 period. The sampling technique used the purposive sampling method with a selected sample of 13 Islamic Commercial Banks registered at OJK in the 2016-2020 period. This research is quantitative research with secondary data sources. The analytical technique chosen in this research is multiple linear regression analysis with IBM SPSS Statistics software version 25. The results show that partially, Islamic Corporate Governance and the amount of core capital had no influence on the market share of Islamic Commercial Banks. On the other hand, the number of service offices affects the market share of Islamic Commercial Banks. Meanwhile, simultaneously, Islamic Corporate Governance, the amount of core capital, and the number of service offices influence the market share of Islamic Commercial Banks in Indonesia.